Nonmesonic weak decay of Λ hypernuclei: The three-nucleon induced mode - Bauer, Eduardo (2017)
The nonmesonic weak decay of 3hypernuclei is studied within a microscopic diagrammatic approach which is extended to include the three-nucleon induced mechanism. We adopt a nuclear matter formalism which, through the local density approximation, allows us to model finite hypernuclei, a one-meson-exchange weak transition potential and a Bonn nucleon–nucleon strong potential. One-, two-and three-nucleon induced weak decay rates are predicted for 123Cby including ground state correlations up to second order in the nucleon–nucleon potential and the recoil of the residual nucleus. Three-nucleon stimulated decays, 3NNN→nNNN(N=nor p), are considered here for the first time. The obtained decay rates compare well with the latest KEK and FINUDA data. The three-nucleon induced rate turns out to be dominated by nnp-and npp-induced decays, it amounts to ∼7%of the total nonmesonic rate and it is ∼1/2of the neutron-induced decay rate. The reduction effect of the nuclear recoil is particularly relevant for the three-nucleon induced rates (∼15%), less important for the two-nucleon induced rates (∼4%) and negligible for the one-nucleon induced rates. Given the non-negligible size of the three-nucleon induced contribution and consequently its importance in the precise determination of the complete set of decay rates, new measurements and/or experimental analysis are encouraged.